Prevalence and risk factor of anemia among pregnant women admitted in antenatal ward in PBMH Bhubaneswar, Odisha - Sobhna Pradhan; Tanupama Karna; Debaleena Singha; Piyali Bhatta; Kalyani Rath; Anasuya Behera (Journal of Family Medicine and Primary Care)
Background: Anemia is one of the contributing factors for morbidity and mortality during pregnancy in developing country including India, which eventually leads to fetal and maternal consequences. Growing fetus depends completely on mothers for all its growth and maturity. Anemia is one of the nutritional deficiency disorders and around 56% of women are suffering from anemia in India. It is one of the reasons for maternal deaths and fetal complication during pregnancy. Aim: The aim of the study was to assess the prevalence of anemia and to determine the risk factors of anemia among pregnant women in PBMH hospital, Bhubaneswar, Odisha. Materials and Methods: A descriptive cross-sectional study was conducted over a period of 1 month from October 11, 2022, to November 11, 2022, from the Department of Obstetrics and Gynecology of Pradyumna Bal Memorial Hospital KIMS, Bhubaneswar. A total sample comprised of 52 pregnant women who were interviewed by using self-structured questionnaire for data collection and classification of anemia was performed according to the Indian Council of Medical Research (ICMR) criteria. Results: A total of 52 antenatal mothers were admitted during this study period (October 11, 2022, to November 11, 2022), and all were selected as study sample. The incidence of anemia among antenatal mother in PBM hospital was found as follows: 17 (33%) mild, 04 (07%) moderate, and 02 (04%) were severe in this present study. The most common indication of anemia among antenatal mother as per the present study was found to be H/O infection (21%), chronic malaria (15%), hook worm (27%), and birth interval (42%). Conclusion: The study implies that the prevalence rate of Anemia is high, that is, 44.2%. Spacing between pregnancy and H/O infection plays a significant role in considering anemia in pregnant women, which eventually affects both maternal and fetal condition.